Strength characteristics of iron ore tailing concrete - Saleh, Abd. Latif (2015)
Materials used in proportioning of concrete have significant impact on the properties of concrete produced. Iron ore tailings (IOTs) is a waste product generated from the production process of iron ore. In this study, IOTs is used as partial replacement for natural sand in the production of normal strength concrete. Samples of Iron ore tailings from two different mines in Kota Tinggi were collected. The Physical properties of natural sand and these Iron ore tailings were determined. The Energy Dispersive X-ray Spectroscopy (EDS) and the microscopic image of these materials were also studied. Normal strength concrete was designed based on water/cement ratio of 0.54 and cement content of 463Kg/m3 was used in preparing the fresh concrete. For each kind of Iron ore tailings concrete, four different types of concrete samples were produced. The percentage of Iron ore tailings as partial replacement for sand in the sample was varied from 10% to 40% at 10% interval. For each concrete sample, the average of three cubes, three cylinders and three prism specimen results was used for the determination of the compressive strength, splitting tensile strength and the flexural strength respectively. Also studied are the water absorption, the ultrasonic pulse velocity and the mode of failure of the IOTs concrete compared with the normal strength concrete. The concrete sample CZT30 containing 30% IOTs recorded the highest 28days compressive strength of 43.7 N/mm2.